Effect of caffeine ingestion after creatine supplementation on intermittent high-intensity sprint performance - Lee, C. -L.; Lin, J. -C.; Cheng, C. -F. (European Journal of Applied Physiology, 2011)
The aim of this study was to investigate the effects of acute caffeine ingestion on intermittent high-intensity sprint performance after 5 days of creatine loading. After completing a control trial (no ergogenic aids, CON), twelve physically active men were administered in a double-blind, randomized crossover protocol to receive CRE + PLA (0.3 g/kg/day of creatine for 5 days then followed by 6 mg/kg of placebo) and CRE + CAF (0.3 g/kg/day of creatine for 5 days and followed by 6 mg/kg of caffeine), after which they performed a repeated sprint test. Each test consisted of six 10-s intermittent high-intensity sprints on a cycling ergometer, with 60-s rest intervals between sprints. Mean power, peak power, rating of perceived exertion (RPE), and heart rates were measured during the test. Blood samples for lactate, glucose, and catecholamine concentrations were drawn at specified intervals. The mean and peak power observed in the CRE + CAF were significantly higher than those found in the CON during Sprints 1 and 3; and the CRE + CAF showed significantly higher mean and peak power than that in the CRE + PLA during Sprints 1 and 2. The mean and peak power during Sprint 3 in the CRE + PLA was significantly greater than that in the CON. Heart rates, plasma lactate, and glucose increased significantly with CRE + CAF during most sprints. No significant differences were observed in the RPE among the three trials. The present study determined that caffeine ingestion after creatine supplements augmented intermittent high-intensity sprint performance.